2017
DOI: 10.7554/elife.28034
|View full text |Cite
|
Sign up to set email alerts
|

Principles of cellular resource allocation revealed by condition-dependent proteome profiling

Abstract: Growing cells coordinate protein translation with metabolic rates. Central to this coordination is ribosome production. Ribosomes drive cell growth, but translation of ribosomal proteins competes with production of non-ribosomal proteins. Theory shows that cell growth is maximized when all expressed ribosomes are constantly translating. To examine whether budding yeast function at this limit of full ribosomal usage, we profiled the proteomes of cells growing in different environments. We find that cells produc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

38
293
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(333 citation statements)
references
References 62 publications
38
293
2
Order By: Relevance
“…Discussion A central theme emphasized in this study is mechanisms by which cells manage resource allocation, supply and demand during cell growth. Recent studies in model organisms like yeast and E. coli focus on protein translation, and the need to 'buffer' translation capacity during cell growth (Hui et al, 2015;Metzl--Raz et al, 2017). These studies alter our perception of how translation is regulated during high cell growth.…”
Section: Gcn4 Dependent Lysine and Arginine Supply Is Essential To Mamentioning
confidence: 99%
See 1 more Smart Citation
“…Discussion A central theme emphasized in this study is mechanisms by which cells manage resource allocation, supply and demand during cell growth. Recent studies in model organisms like yeast and E. coli focus on protein translation, and the need to 'buffer' translation capacity during cell growth (Hui et al, 2015;Metzl--Raz et al, 2017). These studies alter our perception of how translation is regulated during high cell growth.…”
Section: Gcn4 Dependent Lysine and Arginine Supply Is Essential To Mamentioning
confidence: 99%
“…Such a balanced cellular economy therefore entails multiple regulatory systems that sense nutrients, and control global responses in order to manage metabolic resources and ensure coordinated growth outputs. Here, the model eukaryote, Saccharomyces cerevisiae, has been instrumental in building our general understanding of global nutrient--dependent responses, for identifying what are 'limiting metabolites' for a cell, addressing resource allocations within cells, as well as to uncover conserved mechanisms of nutrient--sensing (Boer et al, 2010;Brauer et al, 2006;Dikicioglu et al, 2011;Gresham et al, 2011;Gutteridge et al, 2010;Metzl--Raz et al, 2017;Saldanha et al, 2004;Zaman et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the proteins involved in the synthesis of the major lipid components, the fatty acids and sterols, were enriched among the high and moderate abundant proteins, whereas the proteins related to the synthesis of specific lipid head groups were enriched in the low to very low abundant proteins. This might be a consequence of cell resource optimization as protein synthesis is one of the most energetically expensive tasks in cells 34 . Our lipid map also showed that TG, PC and PE are the most diverse classes of lipids.…”
Section: Discussionmentioning
confidence: 99%
“…indicates an increasing overcapacity of ribosomes with a decreasing growth rate µ Metzl-Raz et al, 2017). Both parameters w R and φ R,0 were determined for E. coli by fitting equation (2) to measured, cross-conditional concentration data of the ribosomal proteome sector ( Fig 2B).…”
Section: The Ribosomal Sectormentioning
confidence: 99%